Linguistic research at Samara University: traditions and perspectives - N. A. Ilyukhina; M. V. Cherkunova; S. I. Dubinin (Вестник Самарского университета: История, педагогика, филология)
The article provides a thorough description of the scope, the content and the results of the research carried out at Samara University by the three linguistic departments of Philology and Journalism Faculty. The authors offer an exhaustive insight into the 50 years’ history of language studies performed by the lecturers of the Russian Language and Mass Communication Department, the English Philology Department and the German Philology Department. Long-standing research traditions, current trends as well as future prospects are summarized within the scientific framework of each department. The formation and development of scientific schools are traced alongside the overview of the main current research fields and the most significant results of the cooperative work. Synergistic and integrative character of inter-departmental collaboration is specifically highlighted as the means of promoting the joint scientific result to the highest degree. Large-scale work in the sphere of linguistic science popularization is showcased. Besides, systematic process of nurturing highly qualified scientific personnel is presented. When analyzing research in the field of Russian studies, special attention is paid to the input of T.P. Romanova into the study of Russian onomastics.